Rookie of the year [videorecording (DVD)] - Nicholas, Thomas Ian; Busey, Gary; Hedaya, Dan; Stern, Daniel, 1957- (20th century Fox family feature, 2001)
When the cast is removed from his severely broken arm, a clumsy 12-year-old is shocked to find his arm has become a 100 mile-per-hour thunderbolt, and is signed as ace pitcher for the Chicago Cubs.